O6-methylguanine DNA methyltransferase (MGMT) expression in U1242 glioblastoma cells enhances in vitro clonogenicity, tumor implantation in vivo, and sensitivity to alisertib-carboplatin combination treatment - Müge Sak; Müge Sak; Brian J. Williams; Brian J. Williams; Andrew J. Hey; Mayur Sharma; Leslie Schier; Megan J. Wilson; Mahatma Ortega; Alyssa I. Lara; Mikaela N. Brentlinger; Norman L. Lehman; et al. (Frontiers in Cellular Neuroscience)
Glioblastoma (GBM) is the most common and aggressive primary adult CNS tumor. Increased understanding of glioma biology is needed for novel treatment strategies and maximization of current therapies. The action of the widely used antiglioma drug, temozolomide (TMZ), relies on its ability to methylate DNA guanine bases leading to DNA double strand breaks and apoptosis. However, glioma cells capable of reversing guanine methylation via the repair enzyme O6-methylguanine DNA methyltransferase (MGMT) are resistant to TMZ. GBMs exhibiting high MGMT expression, reflected by MGMT gene promoter hypomethylation, respond poorly to both chemo- and radiation therapy. To investigate possible non-canonical biological effects of MGMT and develop a tool to investigate drug sensitivity and resistance, we generated MGMT knockout (KO) U1242 GBM cells. MGMT KO U1242 cells showed substantially increased sensitivity to TMZ in vivo, and unlike wildtype U1242 cells, failed to form tumors in nude mouse brains. They also showed reduced growth in soft agar, as did wildtype U1242 and additional glioma cell lines in which MGMT expression was knocked down by siRNA. MGMT thus possesses cellular functions related to tumor cell engraftment and anchorage-independent growth beyond guanine methyltransferase repair. We additionally show that the combination of the AURKA inhibitor alisertib and carboplatin selectively induces apoptosis in high MGMT expressing wildtype U1242 cells versus MGMT KO U1242 cells and extends survival of mice orthotopically implanted with wildtype U1242 cells. This or other platinum-based drug combinations may represent a potentially effective treatment approach to chemotherapy for GBM with MGMT promoter hypomethylation.